Inter-room transmission of pollutants in street canyons - Turabbhai Mohammadi, Murtaza (2024)
Clean air is a fundamental requirement for health and wellbeing and has been incorporated as one of the 15 Sustainable Development Goals set by the World Health Organisation. Epidemiological studies have highlighted the role of polluted air and the flow of contaminants via airborne routes in spreading diseases and causing ailments. Episodic scenarios in the past, such as gas leaks, fires, epidemics etc., have further shed light on routes of airborne transmission of pollutants and pathogens, which can endanger the health of urban dwellers. More recently, the SARS pandemic in 2002 and the COVID-19 pandemic in 2020 have pointed out the airborne spread of pathogens within the built environment which can compromise human safety. It is thus necessary to understand the routes of pollutant transmission in buildings and urban habitats before any strategic intervention can be introduced to limit their spread.